The Endangered Species Act - Doub, J. Peyton (Taylor & Francis, 2025)
The complex regulations of the Endangered Species Act can be challenging for environmental professionals who must comply with them or assist clients in compliance. This volume discusses the Act using clear scientific prose that all professionals can readily comprehend. It explores the history and the basic scientific theory underlying the Act. It provides an overview of its key provisions and examines the Act in the context of other key environmental planning statutes. The book also details the regulatory processes faced by other government agencies and private developers who must routinely ensure that their actions are in compliance.